PERLINDUNGAN WARISAN BUDAYA SENI TARI MELINTING MASYARAKAT ADAT LAMPUNG DALAM PERSPEKTIF SISTEM HUKUM KEKAYAAN INTELEKTUAL - Reza Aditya Ramadhan (Indonesia Private Law Review, 2020)
The existence of Melinting Dance as a traditional dance from East Lampung Regency does not get maximum protection against local communal intellectual property. The problem in this article is What is the protection of intellectual property law against Traditional Cultural Expressions? What is the role of the Lampung provincial government in protecting intellectual property against the communal rights of the traditional dance of Lampung Province? This research is intended to find a model of protection for the Melinting Dance. This research uses a Normative and Empirical Juridical approach.The research results found that the Protection of Intellectual Property Laws against Traditional Cultural Expressions is carried out by the government by making regulations Law No. 28 of 2014 concerning Copyright. To protect the masterpiece of Indonesian indigenous peoples, the Ministry of Education and Culture of the Republic of Indonesia has designated the Indonesian Intangible Cultural Heritage. The role of the Lampung Province government in protecting intellectual property against the communal rights of the traditional dance of Lampung Province consists of a normative role, namely by making regulations concerning the Protection of the Lampung People Intellectual. The ideal role of the Lampung Province government is by subjects and extracurricular in the school program, so children today do not forget the inheritance of their ancestors' culture. The factual role that is as an effort to protect and preserve the Melinting dance is done by holding activities such as the Traditional Festival, in various activities to be known by the public and also to show the existence of the Melinting Dance is maintained.As for the suggestions that can be conveyed in this study, the government and the House of Representatives of the Republic of Indonesia as the executive and legislative branch should immediately pass the Law on the Protection and Utilization of Intellectual Property Rights of Traditional Knowledge and Traditional Cultural Expressions. The Lampung Provincial Government should immediately realize the regional regulations governing art as a relic of the people of Lampung.